Polymer dual ring resonators for label-free optical biosensing using microfluidics - Mohd Salleh, Mohd Hazimin; Glidle, Andrew; Sorel, Marc; Reboud, Julien; Cooper, Jonathan M. (Royal Society of Chemistry, 2013)
We demonstrate a polymer resonator microfluidic biosensor that overcomes the complex manufacturing procedures required to fabricate traditional devices. In this new format, we show that a gapless light coupling photonic configuration, fabricated in SU8 polymer, can achieve high sensitivity, label-free chemical sensing in solution and high sensitivity biological sensing, at visible wavelengths